Peran Maneleo Dalam Penyelesaian Konflik di Desa Busalangga Timur, Kecamatan Rote Barat Laut, Kabupaten Rote Ndao - Julio Canra Adu; Ananias Riyaon P. Jacob; Boli Tonda Baso (Jurnal Hukum dan Sosial Politik, 2025)
This research is entitled "The Role of Maneleo in Conflict Resolution in East Busalangga Village, Northwest Rote District, Rote Ndao Regency". The main focus of this research is to examine in depth the role of Maneleo, which is the term for the highest tribal chief in the traditional social structure in East Busalangga Village, in resolving conflicts that occur within the community. Each leo or tribe in this village has its own social structure, with the highest layer called mana leo (leo mane), who holds the highest authority in customary decision-making. The purpose of this research is to determine the role of Maneleo in resolving conflicts according to customary law in East Busalangga Village. The research uses a descriptive method with a qualitative approach, so that it is able to describe the real conditions in the field based on data obtained from interviews, observations, and documentation. The results of the study indicate that Maneleo has a central role in the conflict resolution process. Although the village head, traditional head, and community leaders are involved in the mediation and discussion process, the final decision remains in the hands of Maneleo. Their roles include mediation (compromise), unifying conflicting communities (unifying), and preserving customary and cultural values (adat/budaya). With a deep understanding of customary norms and social conditions, Maneleo are able to resolve conflicts peacefully, maintain harmony, and prevent divisions within the community. This research confirms that Maneleo are not merely symbols of customary leadership, but key figures in maintaining local social and cultural stability. This role also demonstrates that customary-based conflict resolution mechanisms remain highly relevant in rural communities, particularly in the Rote Ndao region.